Prevalence of carotid artery calcification detected by different dental imaging techniques and their relationship with cardiovascular risk factors, age and gender - Tobias Möst; Linus Winter; Yili Elisabeth Ballheimer; Christian Kappler; Magdalena Schmid; Werner Adler; Manuel Weber; Marco Rainer Kesting; Rainer Lutz (BMC, 2023)
Abstract Background Atherosclerosis and its secondary diseases display a major threat to patient's health. Sequelae, like carotid artery calcification (CAC), usually develop over decades and remain asymptomatic for a long time, making preventive measures to reduce mortality and morbidity extremely important. Through panoramic radiography (PR) and cone beam computed tomography (CBCT), dentists may have helpful tools in aiding the holistic care of patients. In this context, the correlation of atherosclerotic risk factors and CAC development have not yet been sufficiently investigated. Thus, the aim of this observational radiological study was to evaluate the diagnostic value of PR compared with CBCT for the detection of CAC in patients older than 60 years. The radiological findings were correlated with gender, age, and cardiac risk factors. Methods PRs and CBCTs of N = 607 patients were used for the qualitative analysis and compared. Basic patient information such as age, gender, body mass index (BMI), smoking history as well as patient's detailed medical history, including heart disease and cardiovascular risk factors such as hypercholesterolemia, arterial hypertension and diabetes mellitus type II were documented and their relation to CAC provided by radiological data was estimated in the form of odds ratios (OR), which were calculated using logistic regression models. Proportions of CAC in different risk groups were compared using Fisher's exact test, the significance level was set to α ≤ 0.05. The interrater reliability of two physicians was estimated using Cohen's kappa. Results With an accuracy of 90.6%, a sensitivity of 67.5% and a specificity of 99.5% compared to CBCT, PR was a reliable method for the diagnosis of CAC. The overall detection rate for CAC was 27.8% across all age groups. Age (OR: 1.351; p = 0.021), the male sex (OR: 1.645; p = 0.006), arterial hypertension (OR: 2.217; p = < 0.001), heart disease (OR: 1.675; p = 0.006), hypercholesterolemia (OR: 1.904; p = 0.003) and chronic obstructive pulmonary disease (OR: 2.016; p = 0.036) were statistically significant risk factors. When correlated, neither history of stroke nor nicotine abuse showed any statistical significance. Conclusions Due to the capabilities of PR in the diagnosis of CAC, dentists can play a vital role in the early diagnosis of vascular disease. Awareness should therefore be raised among dentists regarding the detection of CAC in patients over 60 years of age, with a particular focus on those with arterial hypertension and hypercholesterolaemia.